Are seronegative patients with rheumatoid arthritis and clinically suspect arthralgia properly represented in randomized clinical trials? - D’Onofrio, Bernardo; Selmi, Carlo; Gremese, Elisa (Clinical rheumatology, 2025)
Rheumatoid arthritis (RA) is a chronic immuno-inflammatory disease whose outcomes can vary greatly from one patient to another. One of the main prognostic factors is the presence of serum autoantibodies, such as rheumatoid factor (RF) and anti-citrullinated peptide antibodies (ACPA). Indeed, when seropositive, patients with RA are at higher risk of radiographic progression, disability, and increased mortality. Moreover, while the introduction of the 2010 American College of Rheumatology/European Alliance of Associations for Rheumatology (ACR/EULAR) classification criteria has allowed for an earlier diagnosis, studies on large early arthritis cohorts have also shown that these criteria are less capable of identifying seronegative patients, who are therefore at a higher risk of being diagnosed and treated late. In light of these, the major randomized controlled trials have mostly enrolled patients with autoantibody-positive disease. However, in recent years, it became evident that the two serotypes of RA differ significantly from many points of view. Alongside this, a greater understanding of the disease pathogenesis, particularly the presence of antibodies in patients’ serum even before the onset of arthritis, has generated significant interest in exploring whether the disease could be prevented by treating patients in the pre-arthritis phases. Once again, emerging trials predominantly enroll subjects positive for RA autoantibodies, potentially overlooking seronegative individuals with arthralgia-at-risk.